DIGITAL MARKETING STRATEGY FOR COMPETITIVE ADVANTAGE BUSINESS - Guntarayana, Indria; Wiludjeng, Ferida Asih; Jatimurti, Nugraha (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
The Influence of Digital Marketing on Competitive Advantage and Performance of Micro, Small, and Medium Enterprises (MSMEs) in Blitar Regency. The purpose of this study was to determine the influence of digital marketing on competitive advantage. The research method used was a mixed-method survey with 100 flower seller respondents in Blitar Regency. The analysis results indicate that digital marketing has a positive and significant effect on competitive advantage